1998
DOI: 10.1002/hep.510270615
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of hepatocellular carcinoma with diabetes mellitus after hepatic resection

Abstract: We evaluated the effect of diabetes mellitus on the prognosis of hepatocellular carcinoma after an elective hepatic resection. Of the 342 patients who underwent a hepatic resection between April 1985 and March 1995, 87 (25.4%) were diabetic. Postoperative morbidity was more common among diabetics than among nondiabetics (36.0% vs. 22.5%, P ‫؍‬ .0239). The postoperative survival rate and the cancer-free survival rate were also better in patients without diabetes than in those with diabetes (P ‫؍‬ .0333, P ‫؍‬ .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
74
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 22 publications
7
74
2
1
Order By: Relevance
“…In the present study, we identified the presence of diabetes as a factor significantly contributing to the recurrence of HCC and long- term overall survival after surgical treatment. The results are consistent with findings of Ikeda et al (Ikeda et al 1998). They evaluated 342 HCC patients who underwent a hepatic resection.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, we identified the presence of diabetes as a factor significantly contributing to the recurrence of HCC and long- term overall survival after surgical treatment. The results are consistent with findings of Ikeda et al (Ikeda et al 1998). They evaluated 342 HCC patients who underwent a hepatic resection.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the incidence of DM was 30%, which was similar to findings of Toyoda et al with an incidence of 25.4% (Toyoda et al 2001). In a review of the related literature, rates of DM in HCC patients ranged 15% ~ 30% (Ikeda et al 1998;Huo et al 2004;Fattovich et al 2004;Komura et al 2007;Kawamura et al 2008). However, the incidence of diabetes was found to be higher among HCC patients who received hepatic resection.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…ies found an increased recurrence of HCC in patients with DM [17,30]. We could not analyze the HCC recurrence rates due to the limitation of the cancer registry, but LCS and LDS were both associated with DM.…”
Section: Discussionmentioning
confidence: 89%